Pemberian Pakan Berbeda Terhadap Pertumbuhan Tukik Penyu Sisik (Eretmochelys imbricata) di Pantai Tikus Emas, Sungailiat - Dinda Rinanda; Budi Afriansyah; Ahmad Fahrul Syarif (Jurnal Sumberdaya Akuatik Indopasifik, 2022)
Turtle is reptile that live in the sea and be able to migrate long distances along the Indian Ocean, Pacific Ocean and Southeast Asia. This study was carried out the effect of different feeding on the growth of hawksbill juveniles (Eretmochelys imbricata) at Tikus Emas Beach Sungailiat, Bangka Regency. The study was using the experimental method with Completely Randomized Design (CDR) for 12 weeks with two treatments, namely A (commercial feed in the form of pellets) and B (lemuru fish). Each treatment getting three repetitions using 30 juveniles. Based on the acquired results of our research showed highly significant differences of carapace length P=0,000 (P<0,05) in treatments, as of: (A) 8,65 cm; (B) 10,57cm. There were significant differences on the carapace width P=0,000 (P<0,05), such as: (A) 9,20 cm; (B) 11,51 cm. Body weight showed significant differences P=0,001 (P<0,05) in treatments, as follows: (A) 95,3 g; (B) 211,8 g. Environmental factors that most influence the growth of body weight and length of carapace is water temperature, while the growth of carapace width is pH. In conclusion, lemuru fish (Sardinella lemuru) feed and pellet feed had no significant effect on the carapace length and width growth and increase in body weight of hatchlings.